(untitled) (Transmediterranean History, 2019)
The contribution deals with an account preserved in the Chronica muzarabica or Chronicle of 754. It discusses a failed alliance between the Aquitanian dux, Eudo, and the Berber Munnuz, as well as Eudo’s subsequent cooperation with the Frankish mayor of the palace, Charles Martel. The article analyses how both alliances are presented in various chronicles and places them in the overall context of two expanding forces on the Muslim and Frankish sides.